2005
DOI: 10.1038/ncpcardio0224
|View full text |Cite
|
Sign up to set email alerts
|

Staged endovascular treatment for complicated type B aortic dissection

Abstract: Antihypertensive therapy; staged thoracoabdominal and branch vessel endoluminal repair (STABLE procedure), with stabilization of the dissection and rescue of renal function; CT imaging surveillance to monitor for any further complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 12 publications
1
67
0
2
Order By: Relevance
“…Indications for treatment in the overall patient group and by dissection symptom status are presented in Table III. In the overall patient group, the median number of indications was three per patient (range, [1][2][3][4][5]. A majority of patients (77.5%; 31 of 40) presented with impending aortic rupture (indicated by periaortic effusion or hematoma; 20%; 8 of 40) and/or branch vessel malperfusion (obstruction/compromise based on clinical and/or imaging evaluation by the investigative sites; 67.5%; 27 of 40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for treatment in the overall patient group and by dissection symptom status are presented in Table III. In the overall patient group, the median number of indications was three per patient (range, [1][2][3][4][5]. A majority of patients (77.5%; 31 of 40) presented with impending aortic rupture (indicated by periaortic effusion or hematoma; 20%; 8 of 40) and/or branch vessel malperfusion (obstruction/compromise based on clinical and/or imaging evaluation by the investigative sites; 67.5%; 27 of 40).…”
Section: Resultsmentioning
confidence: 99%
“…5 Nienaber et al 6 subsequently described 12 instances (from a series of 100 patients), where persistent true lumen collapse was present after endograft coverage of the proximal entry tear and were treated with bare metal scaffolding stents. They concluded that scaffolding the distal thoracoabdominal aorta restored flow to malperfused branch vessels and induced positive aortic remodeling.…”
mentioning
confidence: 99%
“…In light of this, some investigators have advocated the placement of bare stents into the distal thoracic aorta to provide structural stability without risking occlusion of intercostal arteries. 91 Finally, it is becoming clear that adoption of this relatively new treatment modality involves an inherent learning curve that affects not only physicians who perform endovascular procedures but also equipment designers and manufacturers. Eggebrecht et al, 68 in their meta-analysis of stent-graft management of type B aortic dissection, reported improved technical success rates in studies published between 2002 and 2004 compared with those published between 1999 and 2001.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…In the uncomplicated chronic or sub-acute setting, subclavian artery revascularization should be performed when the patient has a previous LIMA bypass to a coronary, large segment coverage of the aorta will be performed, dominant vertebral artery on the left, extensive throacoabdominal repair is anticipated in future to help decrease risk of paraplegia. Management is still controversial with some data suggesting that coverage carries an increased stroke and ischemic risk while others use a selective approach to management 13,14 .…”
Section: Operative Managementmentioning
confidence: 99%